KH Mahfud Syaubari's Leadership In Forming The Quality of Salafiyah Islamic Boarding School Education: (Case Study At The Riyadlul Jannah Pacet Islamic Boarding School, Mojokerto, East Java) - Jazwadi, Jazwadi; Kasir, Ibnu (Jurnal Al-Fikrah, 2023)
In this thesis research, to answer the focus of the problem (research questions) by analyzing and revealing the leadership style of the kiai in shaping the quality of education in salafiyah pesantren, the strategies used by the kiai in shaping the quality of salafiyah pesantren education and the implications of the leadership of the kiai in shaping the quality of salafiyah pesantren education. This research uses a qualitative approach with a case study type by taking a single case. Data collection in this study uses participant observation techniques, in-depth interviews, and documentation, the research informants are pesantren administrators, namely the leader of the Riyadlul Jannah Islamic Boarding School Pacet Mojokerto, teachers/asatidz, students and alumni. The data that has been collected is checked for validity by using a triangulation strategy. Technical data analysis is carried out by collecting data, reducing data, displaying data and drawing conclusions. The results of this thesis research are as follows: (1) KH Mahfud Syaubari's Leadership Style in Shaping the Quality of Education in Salafiyah Islamic Boarding Schools is democratic and charismatic, (2) KH Mahfud Syaubari's Leadership Strategy in Shaping the Quality of Salafiyah Islamic Boarding School Education is by: a). Improving the Quality of Human Resources Asatidz and Management, b). Improving the Quality of Santri, (3) Leadership Implications of KH. Mahfud’s Syaubari in Shaping the Quality of Salafiyah Islamic Boarding School is Creating Students who Have Noble Character and are Able to Understand the Classic Books of the Previous Scholars.